Developing a Religion Tolerance-Based Character Education Framework for Elementary School Students - Irbathy, Shafa Alistiana; Mukminin, Moh. Amiril; Yuldashev, Azim Abdurakhmovich; Ramdhan, Tri Wahyudi (Departemen Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2025)
Character education plays a crucial role in shaping students' moral values, especially in multicultural societies where religious tolerance is essential for social harmony. However, fostering religious tolerance in primary schools remains challenging due to limited structured character education programs. This study aims to explore the implementation of religious tolerance-based character education in elementary schools and identify effective strategies for its reinforcement. This study employs a qualitative descriptive approach, with data collected through observations, interviews, and document analysis at an elementary school with a diverse religious background. The data were analyzed using data reduction, display, and conclusion-drawing techniques to understand the phenomenon comprehensively. The findings indicate that strengthening religious tolerance-based character education is implemented through routine activities, spontaneous interventions, teacher role modeling, and environmental conditioning. Routine activities such as daily handshakes, prayers, English Day, literacy sessions, and religious holiday celebrations foster an inclusive school culture. Teachers play a pivotal role in promoting tolerance through direct interventions and exemplary behavior, while the school environment reinforces tolerance through posters, study group arrangements, and discussion-based learning. This study concludes that integrating religious tolerance into daily school activities and the curriculum effectively instills tolerance values among students. These findings contribute to developing structured programs for character education in primary schools, promoting an inclusive and respectful learning environment.